Recoil-ion fractions in collisions of keV Ar+ and Kr+ ions with clean and adsorbate covered GaAs(1 1 0) surfaces - Gayone, Julio Esteban (2002)
Ion scattering and recoiling spectroscopy with time of flight analysis is used to study the ion fractions of Ga and As atoms recoiled in collisions of 5 keV Ar+ and Kr+ with clean GaAs(1 1 0) and with GaAs(1 1 0) covered with H, alkali metals (K and Cs) and fluorides (AlF3). For the case of the clean surface, the Ga ion fraction is positive, large (∼50%) and independent of the projectile type. The As ion fraction is also positive, low for Ar+ (<10%) and relatively large (25%) for Kr+ projectiles. The adsorption of H produces slight changes in both the As and Ga ion fractions, which is in agreement with the adsorption model where H reacts with both As and Ga atoms. The adsorption of alkalis produces strong changes in the ion fractions. At the beginning of the alkali adsorption the neutralization of Ga recoils increases fast with the coverage and follows approximately the variation of the work function. At coverages above half of the saturation value, where the work function has attained a stable value, the ion fraction in Ga remains low (∼10%) and stable while that in As changes, the positive ion fraction decreases and the negative ion fraction increases. This behavior is related to the preferential adsorption sites and the modification of the electronic structure at the surface. The adsorption of AlF3 produces no change in the Ga and As ion fractions for the whole range of coverages investigated (up to full coverage), supporting a non-dissociative and weak reacting model for adsorption.